Concordance between the Mini-Mental State Examination, Short Portable Mental Status Questionnaire and Montreal Cognitive Assessment Tests for Screening for Cognitive Impairment in Older Adults - Campos-Vasquez, F. (2021)
Abstract: Determine the level of concordance between the Mini-Mental State Examination (MMSE), Short Portable Mental State Examination (SPMSQ), and Montreal Cognitive Assessment (MoCA) screening test for cognitive impairment in older adults. A cross-sectional study based on an original cohort study. 1683 patients over 60 years-old were included between 2010 and 2015. Demographic information was collected and the MMSE, MoCA, and SPMSQ scores were obtained. Categorical variables were presented as frequencies and percentages, while numerical ones as median and interquartile range. The agreement was measured and adjusted by the number of years of education by Cohen’s Kappa index (k) with a 95% confidence interval (CI). The agreement was considered as good if k > 0.80. MMSE classified 43.32% of the patients as having cognitive impairment, MoCA 43.14%, and SPMSQ 24.84%. MMSE and MoCA showed an agreement (k) of 0.99 with a 95% CI of 0.99–1.00; MoCA and SPMSQ showed a k of 0.43 (95% CI: 0.38–0.46). Finally, MMSE and SPMSQ showed a k of 0.42 (95% CI: 0.37–0.46). The results did not change when performing the analysis by education subgroups. There was a strong concordance between MoCA and MMSE tests. Nevertheless, the SPMSQ was discordant with the other tests.